Maternal exposure to air pollution and risk of autism in children: A systematic review and meta-analysis - Chun, HeeKyoung; Leung, Cheryl; Wen, Shi Wu; McDonald, Judy; Shin, Hwashin H. (Environmental pollution (1987), 2020)
The number of children diagnosed with autism spectrum disorder (ASD) has been increasing. Previous studies suggested potential association between pregnancy air pollution exposure and ASD. This systematic review and meta-analysis is intended to summarize the association between maternal exposure to outdoor air pollution and ASD in children by trimester based on recent studies. A systematic literature search in 3 databases (Medline, Embase, and Web of Science) was performed using subject headings related to ASD and air pollution since 2007. Eligible studies were screened and evaluated based on predetermined criteria. For meta-analyses, the studies were grouped by air pollutant and exposure time (prenatal period and trimesters). Within-group studies were standardized by log odds ratio (OR) and then combined by three meta-analysis methods: frequentist fixed and random effects models, and Bayesian random effects model. Initial search identified 1564 papers, of which 25 studies remained for final analysis after duplicates and ineligible studies were removed. Of the 25 studies, 13, 14, 12, and 7 studies investigated ASD in children associated with PM2.5, PM10, NO2, and ozone, respectively. The frequentist and Bayesian random effects models resulted in different statistical significance. For prenatal period, frequentist meta-analysis returned significant pooled ORs with 95% confidence intervals, 1.06(1.01,1.11) for PM2.5 and 1.02(1.01,1.04) for NO2, whereas Bayesian meta-analysis showed similar ORs with wider 95% posterior intervals, 1.06(1.00,1.13) for PM2.5 and 1.02(1.00,1.05) for NO2. Third trimester appeared to have higher pooled ORs for PM2.5, PM10, and ozone, but patterns in the time-varying associations over the trimester were inconsistent. For positive association between maternal exposure to ambient air pollution and ASD in children, there is some evidence for PM2.5, weak evidence for NO2 and little evidence for PM10 and ozone. However, patterns in associations over trimesters were inconsistent among studies and among air pollutants. [Display omitted] •Some evidence for positive association between maternal exposure to PM2.5 and ASD.•Weak evidence for positive association between maternal exposure to NO2 and ASD.•Little evidence for association between maternal exposure to PM10 and O3 and ASD.•Inconsistent time-varying associations over trimesters between studies.•Inconsistent time-varying associations over trimesters between air pollutants. A meta-analysis on autism spectrum disorder(ASD) in children and maternal exposure to ambient air pollution found some evidence for PM2.5, weak evidence for NO2 and little evidence for PM10 and ozone.